Wetting of real surfaces - Bormashenko, Edward Yu (De Gruyter, 2013)
"The problem of wetting and drop dynamics on various surfaces is very interesting from both the scientificas well as thepractical viewpoint, and subject of intense research. The results are scattered across papers in journals, sothis workwill meet the need for a unifying, comprehensive work." -- Resumé vydavatele
Keywords: povrchové napětí kapalin; smáčivost; fázové přechody; hystereze; surface tension; wettability; phase exchanges; hysteresis; monografie; elektronické knihy; monographs; electronic books